2017
DOI: 10.1016/j.fuproc.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning behavior of Arsenic in circulating fluidized bed boilers co-firing petroleum coke and coal

Abstract: The emission of Arsenic from coal-fired power plants has generated widespread environmental and human health concerns. This paper discusses Arsenic partitioning from three 440 t/h circulating fluidized bed (CFB) boilers co-firing petroleum coke and coal. All the boilers were equipped with electrostatic precipitator (ESP) or fabric filter (FF), and wet flue gas desulfurization (WFGD). Flue gas was sampled simultaneously both up-and down-stream of the ESP/FF and at the outlet of the WFGD based on EPA Method 29. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Zhu et al ( 2009 ) studied the emission characteristics of trace elements Hg, Pb, Ni, Cr, Cu, and Zn in the co-combustion process of petrochemical sludge and coal on a 0.2MW pilot-scale circulating fluidized bed experimental bench, and found that when the mass ratio of petrochemical sludge to coal increased from 10 to 40%, Hg and Zn emissions increased, while Pb and Ni emissions decreased. Duan et al ( 2017 ) studied the distribution rule of arsenic during the co-processing of petroleum coke by three 440 t/h circulating fluidized bed boilers, and found that As mainly exists in electrostatic dust removal and bag dust removal, accounting for 17.4 to 37.5% and 55.6 to 77.5%, respectively. Morphological analysis shows that As 5+ is the main water-soluble substance in the incoming fuel, bottom ash, and fly ash, while As 3+ is the main water-soluble substance in wet flue gas desulfurization (WFGD) wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al ( 2009 ) studied the emission characteristics of trace elements Hg, Pb, Ni, Cr, Cu, and Zn in the co-combustion process of petrochemical sludge and coal on a 0.2MW pilot-scale circulating fluidized bed experimental bench, and found that when the mass ratio of petrochemical sludge to coal increased from 10 to 40%, Hg and Zn emissions increased, while Pb and Ni emissions decreased. Duan et al ( 2017 ) studied the distribution rule of arsenic during the co-processing of petroleum coke by three 440 t/h circulating fluidized bed boilers, and found that As mainly exists in electrostatic dust removal and bag dust removal, accounting for 17.4 to 37.5% and 55.6 to 77.5%, respectively. Morphological analysis shows that As 5+ is the main water-soluble substance in the incoming fuel, bottom ash, and fly ash, while As 3+ is the main water-soluble substance in wet flue gas desulfurization (WFGD) wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of homogenous mixing, high heat and mass transfer rate and easy control, fluidized bed is applied in various industrial fields, such as petroleum, chemical and energy processes (Van Der Hoef et al 2006). For example, circulating fluidized bed boiler is widely adopted for the co-firing of petroleum coke and coal (Chen and Lu 2007;Duan et al 2017;Cui et al 2018). In actual industrial processes, inert particles such as sand are often added to the bed to assist the fluidization and promote the heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…4 During coal combustion, As and Pb are partially present in the bottom slag and fly ash, and the rest is released into the flue gas during combustion. 5 Most of the As and Pb in the fly ash are removed by a dust removal device, 6 while the As and Pb present in ultrafine particles and the gaseous phase are released into the atmosphere with the flue gas. Thus, the transformation of As and Pb during coal combustion is very important for the development of control technology.…”
Section: Introductionmentioning
confidence: 99%